Implementasi Akidah Islam dalam Pelaksanaan Tradisi Baralek Gadang di Nagari Ujung Gading Kecamatan Lembah Melintang Kabupaten Pasaman Barat - Asnaini, Anita (UIN Sumatera Utara, 2024)
This research is entitled Implementation of Islamic Aqidah in the Implementation of the Baralek Gadang Tradition in Nagari Ujung Gading, Lembah Melintang District, West Pasaman Regency. The background of this research is the implementation of the traditional Baralek Gadang wedding process in Nagari Ujung Gading, Lembah Melintang District, West Pasaman Regency, which is still carried out every time a wedding is held. In the implementation of these wedding customs, there are religious elements and Islamic religious values that can be used as guidelines and examples among the younger generation and the surrounding community.The method used in this study was through field research (Fiel Research) with a descriptive qualitative approach, data collection techniques were processed from direct observation by looking at the implementation of marriages, field interviews with a total of 4 informants and documentation, data analysis was carried out using descriptive analysis which included: data collection, data filtering, data classification and conclusion drawing. The purpose of this study is to find out the process of implementing Baralek Gadang to find out what are the important sequences in the implementation of Baralek Gadang, to find out the implementation of creed values in the implementation of Baralek Gadang. Based on the results of the study it can be concluded that: first the implementation of the Baralek Gadang wedding custom in Nagari Ujung Gading, Lembah Melintang District, West Pasaman Regency.